Transnational Fantômas: The Influence of Feuillade’s Series on International Cinema during the 1910s - Federico Pagello (Belphégor)
This paper analyzes the international distribution of Louis Feuillade’s adaptations of Fantômas novels and their large influence on foreign cinemas. It emphases the global success of Feuillade’s films, as well as the unevenness characterising their reception and assimilation by non-French cultural industries. A highly controversial character and a key player in the relationship between cinema and literature during the crucial years when the feature and serial films boosted and legitimized the film industry, Fantômas is without any doubt an exemplary case study of the transnational and transmediatic circulation of popular fiction.